Frequency of Arrhythmias in Patients with Acute Myocardial Infarction (Medical Forum Monthly, 2024)
Objective: To determine the frequency of arrhythmias in patients admitted with Acute Myocardial Infarction.Study Design: Observational studyPlace and Duration of Study: This study was conducted at the Department of Cardiology, LUH Hyderabad from January 2015 to December 2016.Materials and Methods: Patients with Acute MI, both genders were selected for the study. Acute MI and arrhythmia’s diagnosis was assessed on the basis of history, electrocardiography and arrhythmias, and significantly cardiac enzymes (biomarkers) elevation particularly Troponins. Finally arrhythmias were assessed and all the data was recorded in the proforma.Results: In our study 90 patients were selected, patients mean age was 55.66±10.4 years male gender was most common 69(76.6%). Acute anterior wall MI and Acute inferior MI were found most common as 27.77% and 23.33%. Over all arrhythmias was found 83.40%. According to type of arrhythmias VT, VF, Atrial Fibrillation and CHB were found most common as 26.66%, 13.34%, 14.66% and 14.66% respectively.Conclusion: We concluded that Arrhythmias is most frequent in patients with MI, and found almost all in cases